YouTube as a Learning Media to Improve the Student’s Speaking Ability in 21st Century - Yuli Nurmala Sari; Margana Margana (Journal of English Language Teaching and Linguistics, 2019)
The development of students' skills, especially in speaking, is considered important to get more attention because speaking skill is included as one of the productive skills that requires a lot of practice rather than only learning the theory. In mastering speaking skill, it is regarded necessary to not only understand what others are talking about but also to respond and communicate effectively with others. Thus, a maximum use of instructional media, especially YouTube, is considered necessary in enhancing the development of students’ speaking skill as a crucial capability to be possessed in the 21st century. The purpose of this study is mainly to describe YouTube's maximum use in terms of practice as well as disclose the benefits of using YouTube as a media learning.